2017
DOI: 10.18502/kls.v3i5.990
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Embryo from Basal Leaf Segments of Vanda tricolor Lindl. var. pallida

Abstract: Somatic embryogenesis is one of techniques in plant micropropagation. The induction of somatic embryogenesis through callus phase was done on Vanda tricolor Lindl. var. pallida. This study aimed to find out the effect of naphtalene acetic acid (NAA) and benzyl amino purine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…In orchids, PLBs can be induced directly from explants or indirectly from callus [ 49 , 50 ]. So far, it has not been reported that PLBs of Paphiopedilum can occur directly from explants.…”
Section: Discussionmentioning
confidence: 99%
“…In orchids, PLBs can be induced directly from explants or indirectly from callus [ 49 , 50 ]. So far, it has not been reported that PLBs of Paphiopedilum can occur directly from explants.…”
Section: Discussionmentioning
confidence: 99%
“…Wimber [73] was the first to use leaf segments successfully for in vitro orchid propagation. The leaf culture in monopodial orchids is beneficial as no mother plant is sacrificed, and the explants are available throughout the season [74]. Chookoh et al [75] showed only the inner expanding leaves of Tolumnia Snow Fairy producing protocorm-like bodies (PLBs) on MS medium augmented with 4 mg L −1 BA and 0.5 mg L −1 NAA, while outer leaves showed no in vitro growth response.…”
Section: Micropropagation Employing Different Explantsmentioning
confidence: 99%
“…Basal segment of leaf was cultured on half-strength MS medium + 0.05 mg L -1 NAA + 0.01 mg L -1 BAP (following Hardjo and Savitri, 2017). Subculturing was carried out after 4 wk (week)s intervals.…”
Section: 2 Induction and Regeneration Of Somatic Embryomentioning
confidence: 99%
“…Auxins, especially α-naphtalene acetic acid (NAA) affect the process of regeneration in monopodial orchids, and act synergistically on the formation of PLBs (Jainol and Gansau, 2017). Hardjo and Savitri (2017) succeeded in callus induction from the basal part of V. tricolor var. pallida's leaf using half-strength MS medium (Melviana, et al, 2021b;Murashige and Skoog, 1962) with the addition of 0.05 mg L -1 NAA in collaboration with 0.01 mg L -1 BAP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation